Childhood blindness, Eye disease screening checklist, Primary eye care, Sensitivity and Specificity (2021)
Approximately seventy per 100,000 children are blind worldwide. Early detection and prompt treatment play vital roles in prevention of blindness from cataract and other eye diseases in children. However, there are no established screening programmes for blinding eye diseases among infants in Nigeria. This has contributed to delayed presentation to hospital among children with blinding eye diseases. Therefore, this study was conducted to develop and validate a simple screening tool for the early detection of blinding eye diseases among infants as well as assess the perceptions of health care workers regarding the feasibility of using the tool. This cross-sectional study was conducted in 3 phases. The first phase was the development and validation of a screening checklist. This entailed a literature review, expert opinion, stakeholders’ input, content validation and pretesting of the checklist. The second phase was a diagnostic accuracy study which compared the newly developed checklist to a gold standard, which was eye examination by an ophthalmologist. This phase was carried out on 1214 infants receiving immunisation in eight primary health care centres located in four urban Local Government Areas in Ibadan metropolis. Each infant was first screened by a primary health worker (immunisation staff) using the checklist and subsequently examined by the ophthalmologist. The sensitivity, specificity, positive and negative predictive values as well as reliability indices of the checklist were determined. The third phase was a questionnaire survey to assess the perceptions of all the participating immunisation staff (38 in number) about the feasibility of using the checklist. Data were analysed using descriptive statistics. Level of significance was set at α0.05. A checklist with two sections and 11 items was developed. The first section consisted of six questions that the health workers asked the infants’ mothers or caregivers; while the second section contained five questions that were answered by the health workers after a quick examination of the children’s eyes. The mean age of the infants was 5.2±3.8 months and 52.5% were males. The screening checklist had a sensitivity of 70.0% for detection of blinding eye disease. In addition, it had a specificity of 94.8% for detection of blinding eye disease. The inter-observer agreement was 96.6% (Kappa = 0.71); while test-retest reliability showed an intra-class correlation coefficient of 0.90. All the immunisation staff were females, with a mean age of 43.1±7.6 years. They all reported that the checklist was useful in screening for eye diseases among infants. Majority (81.6%) reported that the checklist was very easy to use. About one-third (34.2%) experienced challenges, such as poor cooperation from mother or child, while using the checklist. A screening tool with good sensitivity, high specificity and high reliability was developed for the early detection of blinding eye diseases in infants. Primary health care workers found the checklist to be easy to administer and useful for screening. Adoption of this checklist as a screening tool at the primary health care level could be instrumental in the establishment of screening programmes and early detection of blinding eye diseases among children.